Histórias de antigamente: cultura e memória nas Lavras Diamantinas - Codes, Sílvia Correia de (2011)
This dissertation aims to understand the importance and function of storytelling in the everyday life of residents of the Caeté-Acu district – located in the region of Lavras Diamantina, State of Bahia. The stories or “tales” such as that of the Werewolf, the Headless mule, the golden Knight, the diamond pot and the “livusias” of the mines, famous in the region, are interpreted here inscribed within the concept of “wonderful”, as described by the French medievalist Jacques Le Goff. From the analysis of these narratives, we seek to understand everyday practices associated with this imaginary, and how they served as pedagogic tools to prescribe and regulate social behavior in old times. Dialoguing with the sources and oral history specialists, we argue that these narratives result from the appropriation and reframing of imagistic representations and discursive traditions of the Iberian world. Finally, we dialogue with the contradictions and doubts posed by residents themselves about the veracity of these “stories”, seeking to understand the viewpoint of the younger generation about these stories and the efforts being waged by some sections of Vale do Capão to preserve these stories from technological interference and other modernizing changes the district has experienced in recent decades. These changes eventually lead to a reduction and, in some cases the complete disappearance of the sightings of wonderful manifestations, as well as a decreased reproduction of the “stories” that represent them.